Plasmonic nanostructure-enhanced Raman scattering for detection of SARS-CoV-2 nucleocapsid protein and spike protein variants - Yeh, Yi-Jui; Le, Trong-Nghia; Hsiao, Wesley Wei-Wen; Tung, Kuo-Lun; Ostrikov, Kostya (Ken); Chiang, Wei-Hung (Analytica chimica acta, 2023)
Epidemiological control and public health monitoring during the outbreaks of infectious viral diseases rely on the ability to detect viral pathogens. Here we demonstrate a rapid, sensitive, and selective nanotechnology-enhanced severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) detection based on the surface-enhanced Raman scattering (SERS) responses from the plasma-engineered, variant-specific antibody-functionalized silver microplasma-engineered nanoassemblies (AgMEN) interacting with the SARS-CoV-2 spike (S) and nucleocapsid (N) proteins. The three-dimensional (3D) porous AgMEN with plasmonic-active nanostructures provide a high sensitivity to virus detection via the remarkable SERS signal collection. Moreover, the variant-specific antibody-functionalization on the SERS-active AgMEN enabled the high selectivity of the SARS-CoV-2 S variants, including wild-type, Alpha, Delta, and Omicron, under the simulated human saliva conditions. The exceptional ultrahigh sensitivity of our SERS biosensor was demonstrated via SARS-CoV-2 S and N proteins at the detection limit of 1 fg mL−1 and 0.1 pg mL−1, respectively. Our work demonstrates a versatile SERS-based detection platform can be applied for the ultrasensitive detection of virus variants, infectious diseases, and cancer biomarkers. [Display omitted] •Plasma-engineered SERS sensors can detectSARS-CoV-2 nucleocapsid and spike antigens in artificial saliva.•Antibody-functionalized SERS sensors can detectSARS-CoV-2 wild-type, Alpha, Delta, and Omicron variants.•The developed SERS sensors can be used asa precise quantitative diagnostic tool.